Copper(II) azido complexes containing trinitrogen ligands: [Cu(?3-L)(N3)]2[Cu2Cl2(N3)4] [L = 2,6-bis(3,4-dihydro-2H-pyrrol-5-yl)pyridine], a tridimensional network of cationic and anionic copper complexes - Cabort, Amel; Therrien, Bruno; Bernauer, Klaus; Süss-Fink, Georg (My University, 2003)
Copper(II) azido complexes contg. a tridentate trinitrogen ligand, [Cu(?3-L)(N3)]+ [L = 2,6-bis(3,4-dihydro-2H-pyrrol-5-yl)pyridine] as well as [Cu(?3-R,S-LH4)(N3)]+, [Cu(?3-S,S-LH4)(N3)]+ and [Cu(?3-R,R-LH4)(N3)]+ [LH4 = 2,6-bis(pyrrolidin-2-yl)pyridine] were synthesized from Cu(ClO4)2·6H2O, NaN3 and the corresponding tridentate ligand and crystd. from methanol as the perchlorate salts. The single crystal x-ray structure analyses show these complexes to form 1-dimensional networks by Cu···N(azide) intermol. interactions, depending on the conformation of the tridentate ligand. In the case of L, an excess of sodium azide gives [Cu(?3-L)(N3)]2[Cu2Cl2(N3)4], the crystal structure anal. of which reveals a surprising tridimensional network of cationic and anionic copper(II) complexes linked by Cu···N(azide) and Cu···N(L) interactions. [on SciFinder(R)]
Keywords: copper azide pyrrolylpyridine pyrrolidinylpyridine complex prepn structure; crystal structure copper azide pyrrolylpyridine pyrrolidinylpyridine complex